Binary coder for pulse code modulation - Paraken, Yuen (1974)
Based on the principle of Sampling Theorem, a binary coder for pulse code modulation is constructed. The investigation deals with the construction and development of the experimental equipment by making use of available components. It is tested under different levels of input voltages, both d.c. and a.c. The construction model employs all solid-state devices. The accuracy of the binary output pulse is analyzed by considering all possible sources of errors. Suggestions for the improvement of the constructed model are proposed.